2018
DOI: 10.1002/jcp.27789
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and unfolded protein response profile in quadriceps of sarcopenic patients with respiratory diseases

Abstract: Impaired muscle strength and mass (sarcopenia) are common in patients with respiratory cachexia, namely chronic obstructive pulmonary disease (COPD) and in lung cancer (LC)‐cachexia. Misfolded/unfolded proteins in endoplasmic reticulum (ER) induce the compensatory unfolded protein response (UPR). Expression of ER stress and UPR markers may be differentially upregulated in vastus lateralis (VL) of patients with respiratory sarcopenia associated with either a chronic condition (COPD) or subacute (LC)‐cachexia. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 61 publications
1
42
0
Order By: Relevance
“…ER stress and disruptions in the UPR, calcium homeostasis, and proteostasis have been reported in clinical and experimental cachexia and other inflammation-driven muscle diseases such as myositis, suggesting a link between increased levels of inflammatory cytokines and ER stress in skeletal muscle [45]. Recent studies have further demonstrated that the markers of ER stress and the UPR are elevated in skeletal muscle in various catabolic conditions, including cancer [46][47][48]. TRAF6 is an E3 ubiquitin ligase and an adaptor protein that is involved in the downstream activation of multiple signaling pathways in response to cytokines and microbial products.…”
Section: Er Stress Upr and Cancer Cachexiamentioning
confidence: 99%
See 1 more Smart Citation
“…ER stress and disruptions in the UPR, calcium homeostasis, and proteostasis have been reported in clinical and experimental cachexia and other inflammation-driven muscle diseases such as myositis, suggesting a link between increased levels of inflammatory cytokines and ER stress in skeletal muscle [45]. Recent studies have further demonstrated that the markers of ER stress and the UPR are elevated in skeletal muscle in various catabolic conditions, including cancer [46][47][48]. TRAF6 is an E3 ubiquitin ligase and an adaptor protein that is involved in the downstream activation of multiple signaling pathways in response to cytokines and microbial products.…”
Section: Er Stress Upr and Cancer Cachexiamentioning
confidence: 99%
“…A recent study by Barreiro et al indicates elevated marker of all the three arms of the UPR in vastus lateralis muscle in lung cancer cachectic patients. However, a caveat of the study was that while non cachectic lung cancer patients should have been used as a control, the comparisons were made with healthy subjects [48]. Intriguingly, instead of providing protection, pharmacological inhibition of ER stress using 4-phenylbutyrate (4-PBA), a chemical chaperone that attenuates ER stress [52,53], was found to exacerbate the loss of muscle mass in LLC tumor-bearing mice.…”
Section: Er Stress Upr and Cancer Cachexiamentioning
confidence: 99%
“…in addition, the mrna and protein expression levels of ATF6 were significantly upregulated in the vastus lateralis (Vl) of patients with lc-induced cachexia, and aTF6 was also discovered to potentially interact with protein degradation pathways, such as the uPS. The gene expression levels of MAFbx and MuRF1 were also significantly upregulated in the Vl of lc-induced cachexia patients compared with healthy controls (124). evidence from previous studies has also revealed that multiple markers of er stress and the uPr, such as PerK, ire1a and aTF6, were highly activated in the skeletal muscle of llc and apc(Min/+) mouse models of cancer cachexia.…”
Section: Er Stress and Mitochondrial Dysfunctionmentioning
confidence: 71%
“…Previous studies have reported emerging roles of er stress and the uPr in cancer cachexia-induced muscle atrophy (31,123,124). in fact, markers of er stress and the uPr were upregulated in the muscles of cachectic patients with cancer (124).…”
Section: Er Stress and Mitochondrial Dysfunctionmentioning
confidence: 91%
“…To further investigate the role of Rcn3 in pulmonary diseases, selective Rcn3 knockout in AECIIs were successfully established in our laboratory, and have been employed to study the function of Rcn3 in the development of lung fibrosis [9]. We hereby established the PPE-induced An accumulation of misfolded and unfolded proteins in ER lumen under physiological or pathological stress results in ER stress [29]. To restore protein homeostasis, the unfolded protein response (UPR) is mediated and activated by ER membrane protein sensors, which were regulated by GRP78 [30,31].…”
Section: Discussionmentioning
confidence: 99%